1995
DOI: 10.1007/bf00969691
|View full text |Cite
|
Sign up to set email alerts
|

Changes in organic solutes, volume, energy state, and metabolism associated with osmotic stress in a glial cell line: A multinuclear NMR study

Abstract: Diffusion-weighted in vivo 1H-NMR spectroscopy of F98 glioma cells embedded in basement membrane gel threads showed that the initial cell swelling to about 180% of the original volume induced under hypotonic stress was followed by a regulatory volume decrease to nearly 100% of the control volume in Dulbecco's modified Eagle's medium (DMEM) but only to 130% in Krebs-Henseleit buffer (KHB, containing only glucose as a substrate) after 7 h. The initial cell shrinkage to approx. 70% induced by the hypertonic stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 52 publications
6
61
1
Order By: Relevance
“…The reduced levels of mI and tau in this study may reflect maintenance of volume regulation for hypo-osmolarity like situation developed due to radiation induced oxidative stress. Results of our study are consistent with another in vitro NMR spectroscopy based study that showed oxidative stress induced reduction in the levels of mI, taurine, hypotaurine in astrocytes 34,36 . Furthermore, studies have suggested the role of microenvironment, in particular, neuroinflammation for inhibition of neurogenesis, which subsequently may contribute to neurocognitive impairment post irradiation 32,38 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reduced levels of mI and tau in this study may reflect maintenance of volume regulation for hypo-osmolarity like situation developed due to radiation induced oxidative stress. Results of our study are consistent with another in vitro NMR spectroscopy based study that showed oxidative stress induced reduction in the levels of mI, taurine, hypotaurine in astrocytes 34,36 . Furthermore, studies have suggested the role of microenvironment, in particular, neuroinflammation for inhibition of neurogenesis, which subsequently may contribute to neurocognitive impairment post irradiation 32,38 .…”
Section: Discussionsupporting
confidence: 92%
“…Astrocytes, like other glial cell are an important component of cellular composition of hippocampus and metabolic processes and biosynthetic activities of astrocytes may be altered when exposed to oxidative stress. In support of it, few studies have reported oxidative stress induced osmotic dysregulation in astrocytic cell lines [34][35][36] . According to Kimelberg 37 , due to poor ATP production during oxidative stress, ATP driven transport and ion pumps/channels such as Na 2+ exchangers might have been impaired resulting in astrocyte cell swelling and lowering the intracellular Na levels.…”
Section: Discussionmentioning
confidence: 93%
“…By this means increased lipid de novo synthesis is confirmed upon cell swelling due to hypo-osmotic stress, while it decreases under hypertonic stress accompanied by cell shrinkage. 227,230 In addition, astrocytic swelling induced by acute hyperammonemic conditions caused a 2-fold elevation of 13 C-label incorporation into fatty acids and the glycerol backbone of lipids from cultured astrocytes, 228,229 which is consistent with a swelling-induced activation of acetyl-CoA carboxylase, the key enzyme in fatty acid synthesis. 231 Glutathione synthesis and metabolism of cysteine and glycine Glutathione (GLT), a tripeptide of cysteine, glycine and glutamate, is the major antioxidant.…”
Section: Other Biosynthetic Processes Contributing To Disposition Of mentioning
confidence: 83%
“…The mean apparent displacement, calculated to be 5 mm, corresponds to the typical dimension of neuronal and glial cells in tissue, although one has to keep in mind that these values are ensemble averages over a spatial extension, which is three orders of magnitude larger than the cell dimensions and in this sense, a crude macroscopic average. In experiments on immobilized cells [35,48,49], it has been shown for water and metabolites that a predominantly intracellular signal is detected at a diffusion weighting larger than approximately b= 5 ms/mm 2 due to the lowered D app when the molecules experience the cell membranes as restrictions and are reflected. In contrast, D app of the extracellular, free or hindered diffusing molecules in the surrounding perfusion medium or in the interstitial space in tissue is near the free diffusion constant and the inherent NMR signal decays fast at small q values.…”
Section: Discussionmentioning
confidence: 99%